2007
DOI: 10.1128/jb.00812-07
|View full text |Cite
|
Sign up to set email alerts
|

The Unusual 23S rRNA Gene of Coxiella burnetii : Two Self-Splicing Group I Introns Flank a 34-Base-Pair Exon, and One Element Lacks the Canonical ΩG

Abstract: We describe the presence and characteristics of two self-splicing group I introns in the sole 23S rRNA gene of Coxiella burnetii. The two group I introns, Cbu.L1917 and Cbu.L1951, are inserted at sites 1917 and 1951 (Escherichia coli numbering), respectively, in the 23S rRNA gene of C. burnetii. Both introns were found to be self-splicing in vivo and in vitro even though the terminal nucleotide of Cbu.L1917 is adenine and not the canonical conserved guanine, termed ⍀G, found in Cbu.L1951 and all other group I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
37
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 39 publications
2
37
0
Order By: Relevance
“…Furthermore, introns are preferentially found in conserved regions of the rRNA genes (21,22), which can explain why the insertion sites of introns analyzed in this study are homologous to locations of introns found in mitochondrial and nuclear rRNA genes of eukaryotes. This is consistent with the hypothesis that introns can be horizontally transferred over large phylogenetic distances (50,51). All ORFs in the introns described here encoded IEPs typical of a common family of homing endonucleases, suggesting that the introns spread into cognate sites as DNA elements via homing (20).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Furthermore, introns are preferentially found in conserved regions of the rRNA genes (21,22), which can explain why the insertion sites of introns analyzed in this study are homologous to locations of introns found in mitochondrial and nuclear rRNA genes of eukaryotes. This is consistent with the hypothesis that introns can be horizontally transferred over large phylogenetic distances (50,51). All ORFs in the introns described here encoded IEPs typical of a common family of homing endonucleases, suggesting that the introns spread into cognate sites as DNA elements via homing (20).…”
Section: Discussionsupporting
confidence: 75%
“…Thus, it is tempting to speculate that large sulfur bacteria are the only group of bacteria accumulating introns in their 16S rRNA genes. However, the presence of introns, even multiple ones, has been described for the 23S rRNA genes of several distantly related bacteria (39,50,51,64,65). This gene bears the same evolutionary importance and conservation as the 16S rRNA gene, which indicates that 16S introns might be at least as frequent as 23S introns.…”
Section: Discussionmentioning
confidence: 99%
“…These genetic elements spread efficiently into an intronless cognate site by a process called homing at the DNA level or by reverse splicing at the RNA level (60). The typical secondary structure of a group I intron consists of about 10 paired (P) elements (59,74). P1 and P10 are complementary to the 5Ј exon and 3Ј exon, respectively, and are collectively called the internal guide sequence (IGS), which the intron uses to locate its 5Ј and 3Ј splice sites (31).…”
mentioning
confidence: 99%
“…These traits are conferred by a biphasic developmental cycle that alternates between a fragile, metabolically active large cell variant (LCV) and a durable, dormant small cell variant (SCV) (8). Even though C. burnetii occupies an acidic parasitophorous vacuole where the opportunity for HGT is likely minimal, its genome contains 29 insertion sequences strewn across the chromosome, two group I introns and an intervening sequence (IVS) within its sole 23S rRNA gene, and a putative intein in the C-terminal region of the replicative DNA helicase (dnaB) gene (59,66).Group I introns self-splice independently of proteins (ribozyme) and are considered a holdover from a primordial RNA world (77). These genetic elements spread efficiently into an intronless cognate site by a process called homing at the DNA level or by reverse splicing at the RNA level (60).…”
mentioning
confidence: 99%
“…In the 23S rRNA gene, an insert region was identified. The insertion exhibited homology to self-splicing group I introns in the 23S rRNA gene of Coxiella burnetii, including a region encoding a homing endonuclease (Raghavan et al, 2007).…”
mentioning
confidence: 99%